PHOTO : IDENTITY AND COMMODITY ON SOCIAL MEDIA INSTAGRAM - Fitri Murfianti (Proceeding IICACS, 2019)
Many social media sites including instagram allow users to create a profile, upload, and share personal information, photos, music, videos, and other multimedia with their friends or followers’ networks. Photos have the ability to bring the image, so the photo becomes a favorite visual medium that is often used as a way of speaking and communicating among fellow netizens in social media instagram. Instagramer enjoyed such opportunity to make themselves visible to, and heard by, diverse audiences. This study is foccused on how people present their identity through their selected photograph in social media instagram. Drawing from the datas, this research has shown that each individual enter the mediated phase of selfrepresentation. Through the visual image of a photograph, the subject of the photo has their own mind to describe what kind of identity they want. Beside that, the creation of this identity is influenced by the pattern of social relations and interaction of the audience of the photographs. In other words, identity is something formed by society. So that